The objectives of Islamic Law connected with rulings of caring for the deadin the light of jurisprudential reasonings (Damascus University Journal for legal sciences, 2024)
Praise be to God, and may blessings and peace be upon the Messenger of God, his family, his companions, and those who follow him. Islamic law has honored man and taken care of his interests in a way that achieves his happiness in this world and the hereafter, and has required him to have rights in all his circumstances, including his rights in the weakest of those circumstances and the ones most in need of consideration, which is the state of death and the conditions that precede it and the conditions that follow it. These are the rulings collected by the jurists in the chapters on funerals or funerals. Chapter on rulings on the dead. This research took the approach of extrapolating those subsidiary rulings and following the jurists’ explanations for them, leading to deducing the comprehensive meanings that constitute the objectives of that jurisprudential chapter, while beginning to root those rulings by explaining their general characteristics, in an introduction, three sections, and a conclusion. The first section dealt with introducing the terms of the title and what is related to them, and in the second section: it explained the type of rulings related to the care of the dead, their ranks, their supports, and the objectives of Sharia in all of that. As for the third section: it dealt with the established objectives in the branches of the rulings on caring for the dead, whether they relate to an interest related to the dead person, or to his family. And those responsible for preparing it, or anything related to living organisms in general, which preserves the safety of the environment and the sustainability of its financial resources. In conclusion, the research reached the following results: Sharia law guaranteed the rights of the dead by establishing a number of obligatory legal provisions established in legislative sources, and supported them by encouraging reward and fearing earthly and afterlife punishment. Most of these rulings were obligatory to ensure that every dead person would benefit from them. In most of the rulings, the right of God is combined with the right of the servant, and the right of God prevails in them, that is, the general right.If the dead person waives in his will any of his obligatory rights and makes a will that would be a loss of his rights or a violation of his sanctity, then his will will not be executed and his rights will not be forfeited, because of the right of God in it. This is a great honor for the human being. One of the most important goals related to the interest of the dead was the goal of honoring, preserving sanctity, preventing insult, and delivering otherworldly benefits to him. As for the purposes related to the non-dead who is being prepared, the most important of them is the purpose of removing hardship and achieving solidarity, assistance, and consolation in words, deeds, and money. Likewise, the purpose of consideration and exhortation is to mention the reality of man and his fate in a way that produces integrity. As for the goals that apply to all living things, they are preserving the natural environment in order to preserve souls and public health. Preventing the waste of natural and financial resources for useless purposes.
Keywords: Special Purposes; Explanations; Funerals; Rulings Of The Dead